A demonstration of the application of the new paradigm for the evaluation of forensic evidence under conditions reflecting those of a real forensic-voice-comparison case. Issue 1 (January 2016) - Enzinger, Ewald; Morrison, Geoffrey Stewart; Ochoa, Felipe
Abstract: The new paradigm for the evaluation of the strength of forensic evidence includes: The use of the likelihood-ratio framework. The use of relevant data, quantitative measurements, and statistical models. Empirical testing of validity and reliability under conditions reflecting those of the case under investigation. Transparency as to decisions made and procedures employed. The present paper illustrates the use of the new paradigm to evaluate strength of evidence under conditions reflecting those of a real forensic-voice-comparison case. The offender recording was from a landline telephone system, had background office noise, and was saved in a compressed format. The suspect recording included substantial reverberation and ventilation system noise, and was saved in a different compressed format. The present paper includes descriptions of the selection of the relevant hypotheses, sampling of data from the relevant population, simulation of suspect and offender recording conditions, and acoustic measurement and statistical modelling procedures. The present paper also explores the use of different techniques to compensate for the mismatch in recording conditions. It also examines how system performance would have differed had the suspect recording been of better quality. Highlights: Evaluation of strength of evidence under conditions reflecting those of a real forensic-voice-comparison case Use of relevant data, quantitative measurements, and statistical models to calculate likelihood ratios Empirical testing of validity and reliability under conditions reflecting those of the case under investigation Exploration of different techniques to compensate for mismatched recording conditions